Molecular Identification of Grouper Fish (Perciformes: Serranidae) Landed From Pangpang Bay, Banyuwangi - Firdha Farah Pramesti; Laksmi Sulmartiwi; Sapto Andriyono (Universitas Bangka Belitung, 2022)
The Pangpang Bay Banyuwangi has a high potential for fisheries, processing and capturing fisheries, especially the order Perciformes of the families Carangidae, Lutjanidae and Serranidae. Grouper (Serranidae) is one of the high-economic marine fish commodities. However, the grouper fishing data in this area is only known as grouper without knowing the type of species. It is challenging to identify grouper species because groupers have a high degree of morphological similarity and colour variation. Therefore, molecular identification is necessary to determine the type of grouper in this region. This study aims to identify the grouper species that landed from Pangpang Bay based on DNA barcoding. In addition, phylogenetic tree analysis between grouper species (Serranidae) was carried out, and genetic distance analysis of the identified species was compared to the NCBI database. Morphological observations on groupers were carried out first, and fish meat samples were taken for experiments on molecular identification. The results of molecular-based identification revealed two grouper species Epinephelus coioides and Cephalopholis miniata. The results of phylogenetic tree reconstruction of the two groupers form a separate clade. The genetic distance between Epinephelus coioides ranged from 0.00-0.122, while the species of Cephalopholis miniata had a genetic distance of 0.00-0.002.